Potential Mechanism for HIV-Associated Depression: Upregulation of Serotonin Transporters in SIV-Infected Macaques Detected by 11C-DASB PET - Shah, Swati; Sinharay, Sanhita; Matsuda, Kenta; Schreiber-Stainthorp, William; Muthusamy, Siva; Lee, Dianne; Wakim, Paul; Hirsch, Vanessa; Nath, Avindra; Di Mascio, Michele; Hammoud, Dima A. (Frontiers in Psychiatry, 2019)
Purpose: Increased incidence of depression in HIV+ patients is associated with lower adherence to treatment and increased morbidity/mortality. One possible underlying pathophysiology is serotonergic dysfunction. In this study, we used an animal model of HIV, the SIV-infected macaque, to longitudinally image serotonin transporter (SERT) expression before and after inoculation, using 11C-DASB (SERT ligand) PET imaging. Methods: We infected seven Rhesus macaques with a neurovirulent SIV strain and imaged them at baseline and multiple time points after inoculation (group A). Pyrosequencing methylation analysis of SERT promoter region was performed. We also measured SERT mRNA/protein in brain single-cell-suspensions from another group (group B) of SIV-infected animals (n=13). Results: Despite some animals showing early fluctuations, 86% of our group A animals eventually showed a net increase in midbrain/thalamus binding potential (BPND) over the course of their disease (mean increased binding between last time point and baseline= 30.2 % and 32.2 % respectively). Repeated-measures mixed model analysis showed infection duration to be predictive of midbrain BPND (p= 0.039). Thalamic BPND was statistically significantly associated with multiple CSF cytokines (P<0.05). There was higher cortical SERT mRNA expression in 2 infected compared to 2 uninfected macaques (4.2 fold) and higher SERT protein levels in the second group (group B) of SIV-infected animals with SIV encephalitis (SIVE) compared to those without SIVE (p=0.014). There were no longitudinal changes in SERT gene promoter region percentage methylation between baselines and last time points in group A animals. Conclusion: Upregulated SERT leading to lower synaptic levels of serotonin is a possible mechanism of depression in HIV+ patients and extrapolating our conclusions from SIV to HIV should be sought using translational human studies.